A Rare Presentation of Sarcoidosis with SIADH: A Case Report (Journal of Medicine, 2016)
We report a case of 60 year old male, who presented with acute change in mental status characterized by lethargy and decreased level of consciousness since one day. Sarcoidosis is a granulomatous disorder of unknown etiology which involves multiple systems. The central nervous system is affected in only 5-15% of patients with sarcoidosis. Neurosarcoidosis is a rare disorder with variable clinical course and prognosis. Treatment consists mainly of high-dose corticosteroids, which usually have to be taken long-term.J MEDICINE January 2016; 17 (1) : 41-42